High level perinuclear antineutrophil cytoplasmic antibody (pANCA) in ulcerative colitis patients before colectomy predicts the development of chronic pouchitis after ileal pouch-anal anastomosis. Issue 5 (1st November 2001) - Fleshner, P R; Vasiliauskas, E A; Kam, L Y; Fleshner, N E; Gaiennie, J; Abreu-Martin, M T; Targan, S R
Abstract : BACKGROUND: The reported cumulative risk of developing pouchitis in ulcerative colitis (UC) patients undergoing ileal pouch-anal anastomosis (IPAA) approaches 50% after 10 years. To date, no preoperative serological predictor of pouchitis has been found. AIMS: To assess whether preoperative perinuclear antineutrophil cytoplasmic antibody (pANCA) expression was associated with acute and/or chronic pouchitis after IPAA. METHODS: Patients were prospectively assessed for the development of clinically and endoscopically proved pouchitis. Serum obtained at the time of colectomy in 95 UC patients undergoing IPAA was analysed for pANCA by ELISA and indirect immunofluorescence. pANCA+ patients were stratified into high level (>100 ELISA units (EU)/ml) (n=9), moderate level (40–100 EU/ml) (n=32), and low level (<40 EU/ml) (n=19) subgroups. RESULTS: Sixty of the 95 patients (63%) expressed pANCA. After a median follow up of 32 months (range 1–89), 32 patients (34%) developed either acute (n=14) or chronic (n=18) pouchitis. Pouchitis was seen in 42% of pANCA+ patients compared with 20% of pANCA− patients (p=0.09). There was no significant difference in the incidence of acute pouchitis between the three pANCA+ patient subgroups. The cumulative risk of developing chronic pouchitis among patients with high level pANCA (56%) before colectomy was significantly higher than in patients with medium level (22%), low level (16%), and those who were pANCA− (20%) (p = 0.005). Multivariate analysis revealed that the sole parameter significantly associated with the development of chronic pouchitis after IPAA was the presence of high level pANCA before colectomy (p=0.005). CONCLUSION: High level pANCA before colectomy is significantly associated with the development of chronic pouchitis after IPAA.